'This is not a posted worker' – short-term cross-border mobility of logistics workers and spatio-temporal dimensions of exploitation in the EU: evidence from the case law of the Court of Justice. Issue 3 (September 2022) - Iossa, Andrea
Abstract: Since the 2018 revision of the Posting of Workers Directive, the debate on posting has once again been heated. The spark comes particularly from disputes concerning cross-border mobility of highly mobile workers employed in transnational logistics services (Dobersberger, FNV, Rapidsped, and to a different extent Gruber and Samidani and AFMB). In this set of case law, the Court of Justice of the EU had to consider whether or not, and to what extent, the workers in question should be considered posted workers. Thus, the case law came to revolve around the spatial and territorial attributes, and the cross-border nature of the work performed. By resorting to the analytical tools provided by legal geography, and in particular to the concept of 'chronotopes of law' elaborated by Mariana Valverde, the aim of this piece is to reflect upon assumptions and implications of the aforementioned rulings with a view of discussing both structural and contingent elements that possibly favour exploitation of posted work in the transnational logistics industry.